Optically transparent membrane based on bacterial cellulose/polycaprolactone - Barud,H. S. (2013)
Optically transparent membranes from bacterial cellulose (BC)/polycaprolactone (PCL) have been prepared by impregnation of PCL acetone solution into dried BC membranes. UV-Vis measurements showed an increase on transparency in BC/PCL membrane when compared with pristine BC. The good transparency of the BC/PCL can be related to the presence of BC nanofibers associated with deposit of PCL nano-sized spherulites which are smaller than the wavelength of visible light and practically free of light scattering. XRD results show that cellulose type I structure is preserved inside the BC/PCL membrane, while the mechanical properties suggested indicated that PCL acts as a plasticizer for the BC membrane. The novel BC/PCL membrane could be used for preparation of fully biocompatible flexible display and biodegradable food packaging.